Mental health literacy among Malaysian youth: exploring multidisciplinary perspectives - Hamzah, Siti Raba’ah; Othman, Intan Nur Suhana; Musa, Siti Nur Syuhada; Mukhtar, Firdaus; Akim, Abdah; Hamzah, Mohammad Rezal (Human Resource Management Academic Research Society, 2022)
The study aimed to explore the opinions of multi-field Malaysian experts on mental health literacy towards youth. Semi-structured interviews were conducted with seven Malaysian experts from psychiatry, clinical psychology, mental health education, and social work. A mixed deductive-inductive thematic analysis was used in the analysis of the qualitative data. The comprehensive view of mental health literacy that emerged from the interviews included i) ability to recognise specific disorders ii) knowledge of how to seek mental health information iii) knowledge of self-treatment and professional help iv) attitude that promotes recognition, v) stigma, and vi) appropriate help-seeking behaviour. To the best of our knowledge, this is the first qualitative study of experts' views of mental health literacy in the context of Malaysian culture. The experts' responses to the interviews generated a comprehensive view of mental health literacy, including several elements that may be salient in Malaysian culture. The results have implications for researchers and practitioners.